(3GdBdF GdaQjOI aj TQM GdbUjOIs - (3CHhYHO Gddg eMeO Hf GdMSf Hf eMeO GdaGSj GdebQjs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf LeGYI ef GdbQGA GdeTJZdjf HbUjOI ddTjN GdEeGe CHj GdbGSe GdTGWHj QMeg Gddg SCdhfj Cf CTQMgG s
(3BNQgG (B:s
(3CQGO GdLeY Hjf GddZJjf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
Keywords: (3GdbQGAGJ hGdJLhjOs